COSO FRAMEWORK: CREDIT UNION PERSPECTIVES - Bernadeth Wanggetete; Marselinus Asri (SIMAK, 2023)
This study analyze the application control of COSO Framework at CU Sauan Sibarrung. Method used on this research were observation and interview on a COSO perspective as a whole function management in CU Sauan Sibarrung. Evaluation risk adequate enough with the existence of policy about supervision on cash receipts and disbursements according to the standards that have specified implementation information and communication on accounting information system in a general manner and still adequate for support internal control. The functions involved, procedures, documents, and records required formed and coordinated such the way in which the information is generated could communicated every day. Activity control carried out to system information accounting adequate. Every transactions and activities has been authorized by authorized staff, monitoring activity to internal control has walked with good and effective. This proven with existing reality where activity walk with good. System authorization proven with document bookkeeping and procedures good record keeping will produce accurate and accessible information trusted about assets, debts, income, and expenses .